2022
DOI: 10.3390/ijerph19127479
|View full text |Cite
|
Sign up to set email alerts
|

Coping with the Experience of Bad Sleep and Fatigue Associated with the Nursing Clinical Practicum

Abstract: Nursing students experience anxiety during clinical practicum, which may interfere with their learning of clinical practice. This study explored the practicum anxiety symptom experience of clinical nursing students. The methodology was a qualitative research design following a grounded theory approach. Research data were gathered via theoretical sampling from 37 female college nursing students practicing in a Central Taiwan hospital and analyzed using the content analysis method. The mean age of the subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Evidence showed that first year nursing students had higher depression rate than fourth year nursing students and by the time they start clinical practice (26). Previous literature showed that a high level of stress in nursing students was associated with depression and anxiety (9,(27)(28)(29). The authors reported that the causes of stressors include unfamiliarity with academic environment, concerns over failure, performance evaluation by the instructors, and ineffective communication with instructors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence showed that first year nursing students had higher depression rate than fourth year nursing students and by the time they start clinical practice (26). Previous literature showed that a high level of stress in nursing students was associated with depression and anxiety (9,(27)(28)(29). The authors reported that the causes of stressors include unfamiliarity with academic environment, concerns over failure, performance evaluation by the instructors, and ineffective communication with instructors.…”
Section: Introductionmentioning
confidence: 99%
“…Nursing students, among the other fields of medical sciences, are exposed to more stressors while studying and they are at high risk of depression more than any other students in non-medical science fields ( 6 ) Depression is associated with disruption of biological rhythms, fatigue, and insomnia ( 9 ). Good mental health is essential for students’ academic performance, concentration, self-efficacy, and quality of life ( 10 ).…”
Section: Introductionmentioning
confidence: 99%